Association among XRCC1, XRCC3, and BLHX gene polymorphisms and chromosome instability in lymphocytes from patients with endometriosis and ovarian cancer - Monteiro, M. S. [UNESP]; Boas, D. B. Vilas; Gigliotti, C. B.; Salvadori, Daisy Maria Favero [UNESP] (Funpec-editora, 2014)
Endometriosis is a complex disease that has both benign and malignant characteristics. It affects 5-10% of women of reproductive age. Studies have demonstrated the existence of common genetic changes in endometriosis and ovarian cancer, suggesting a possible association between these 2 diseases. However, the mechanisms that lead to the development of cancer from endometriosis remain unknown. In this study, we evaluated 3 groups of women: 72 patients with endometriosis, 70 with ovarian cancer, and 70 healthy individuals (controls). Repair (XRCC1 codons 194 and 399, XPD codons 312 and 751, and XRCC3 codon 241)- and metabolism (BLHX codon 443)-related gene polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism technique; the efficiency of DNA damage repair was analyzed in vitro in lymphocytes exposed to bleomycin. The logistic regression model was used to evaluate key associations. The results showed an increased average of chromosome breakage in bleomycin-treated lymphocytes from patients with endometriosis and ovarian cancer compared with healthy women. We also detected significant association between XRCC1, XRCC3, and BLHX polymorphisms and a high frequency of chromosomal damage. Women with endometriosis or ovarian cancer may have an altered mechanism of DNA repair, and these defects may be related to a higher incidence of ovarian cancer.
Keywords: Cancer; Chromosome aberration; DNA repair genes; Molecular epidemiology